Technical efficiency of Boro rice production in Bangladesh: A case of bio-slurry application - Kabir, H; Musharraf, M; Haque, MM; Khan, M (Journal of the Bangladesh Agricultural University, 2016)
The main objective of this study is to estimate the impact of bioslurry to Boro rice production in Bangladesh. Translog production function through Stochastic Frontier Apoproach (SFA) was applied for estimating the efficiency of Boro production. Data were collected from biogas users in the four district of Bangladesh: Mymensingh, Pabna, Thakurgaon and Dinajpur. Biogas users have received significant impact from bio-slurry to Boro rice production while chemical fertilizers have no significant impact to same production. The production efficiency of biogas users is notably different from traditional farms. The efficiency differences are explained mostly by farm size, year of education, family size and off-farm income. Bio-slurry could be applied for reducing application of chemical fertilizers, pesticides and labour requirement that lead to more organic agriculture practices with producing more output, earn more income and save foreign currency. J. Bangladesh Agril. Univ. 13(1): 101-108, June 2015